2014
DOI: 10.1002/cmdc.201402453
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of 1,2,5‐Thiadiazole Carbamates as Potent and Selective ABHD6 Inhibitors

Abstract: At present, inhibitors of α/β-hydrolase domain 6 (ABHD6) are viewed as a promising approach to treat inflammation and metabolic disorders. This article describes the optimization of 1,2,5-thiadiazole carbamates as ABHD6 inhibitors. Altogether, 34 compounds were synthesized and their inhibitory activity was tested using lysates of HEK293 cells transiently expressing human ABHD6 (hABHD6). Among the compound series, 4-morpholino-1,2,5-thiadiazol-3-yl cyclooctyl(methyl)carbamate (JZP-430, 55) potently and irrevers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…Highthroughput approaches, including fluorescence polarization-based ABPP (FluoPol-ABPP; Figure 4b) have been designed to overcome this limitation. 62 Recently, competitive ABPP has led to the discovery of new classes of inhibitors including carbamate, [63][64][65] aza-β-lactams, 66 β-lactones, 67 and reversible piperazine amide 68 (serine hydrolase inhibitors), α-ketoheterocyclic compounds 69 (diacylglycerol lipase inhibitors) and many others. 68 This technique was applied in a study by Yang et al 48 in which they assessed the potency and identified off-targets of the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 orlistat inhibitor of FASN.…”
Section: Competitive Abppmentioning
confidence: 99%
“…Highthroughput approaches, including fluorescence polarization-based ABPP (FluoPol-ABPP; Figure 4b) have been designed to overcome this limitation. 62 Recently, competitive ABPP has led to the discovery of new classes of inhibitors including carbamate, [63][64][65] aza-β-lactams, 66 β-lactones, 67 and reversible piperazine amide 68 (serine hydrolase inhibitors), α-ketoheterocyclic compounds 69 (diacylglycerol lipase inhibitors) and many others. 68 This technique was applied in a study by Yang et al 48 in which they assessed the potency and identified off-targets of the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 orlistat inhibitor of FASN.…”
Section: Competitive Abppmentioning
confidence: 99%
“…We cross-validated the tissue-ABPP findings in gelbased ABPP using homogenates of glioma and control brain. In addition, we used rat cerebellar membranes to facilitate comparison, as previous gel-based ABPP has substantially relied on SH profiling in rodent brain membrane proteomes [14,[19][20][21][22][23][24][25][26][27]. Building on such studies from this and other laboratories [14,[19][20][21][22][23][24][25][26][27], we could identify many of the SH bands based on inhibitor sensitivity and mobility pattern in SDS-PAGE.…”
Section: Comparative Gel-based Abpp Of Sh Activity In Homogenates Of mentioning
confidence: 99%
“…Position of molecular weight markers (in kDa) is indicated on the gel. Based on previous studies from this and other laboratories [14,[19][20][21][22][23][24][25][26][27] many healthy brain-resident SHs were identified, as indicated at left. Note comparable activities of KIAA1363 and LYPLA1/2 doublets (black asterisk) in control brain and glioma.…”
Section: Tissue-abpp Combined With Immunohistochemistry Enables Subcementioning
confidence: 99%
“…Cells were harvested by centrifugation at 8,000 x g for 10 minutes at 4˚C, washed once with PBS, and stored at -80˚C for analysis. [19][20][21] . Both of these assays have major deficits that hinder the speed and accuracy of structure-activity related drug design.…”
Section: Methodsmentioning
confidence: 99%
“…ABHD6 expression negatively regulates AMPA subunit surface expression 46 , and in a mouse model of multiple sclerosis, it was found that therapeutic effects seen by ABHD6 inhibition are mediated through the activation of the CB2 receptor. 45 Overall ABHD6 is a very attractive drug target, but only a few specific inhibitor chemotypes have been identified so far, namely triazoleureas 19 , glycine sulfonamides 20 , and thiadiazole carbamates 21 . In the absence of the ABHD6 atomic structure, biochemical characterization through mutational and functional analysis is key in the continued progression and improvement in developing potent, selective ABHD6-inhibitors.…”
Section: List Of Abbreviationsmentioning
confidence: 99%